Graduates’ employment according to vocational education institutions monitoring - L. M. Serova; K. A. Mazaeva (Высшее образование в России, 2022)
The article presents the monitoring results of vocational education institutions graduates’ employment in 2012 in terms of territory, aggregated occupation groups, types of economic activity, business levels and profession groups.